(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article discusses the types of linguistic gender symbols and the general principles of their use in the process of creating modern models of masculine and feminine principles in the speech of English, Russian and Uzbek speakers. However, in Russian the generic category is one of the main morphological features of the noun, while in English the category of the stem is not so important. It is aimed at identifying similarities and differences in the use of Russian, English and Uzbek lexical units in linguistics. In this article, we also focus on the analysis of the social status of women and men in the context of folk wisdom and language culture, using the example of English, Russian and Uzbek articles. Therefore, Russian, English and Uzbek proverbs were used as examples.